ECONOMIC PROSPECTS OF CULTURAL HERITAGE (MSW Management Journal, 2024)
This research article aims to illustrate some of the benefits brought by developing awareness on the topic of heritage conservation, namely economic profitability. The methodology of this paper compares and evaluates distinct examples, articles and arguments using mainly qualitative methods with some use of quantitative data to reach findings on how to capitalise on opportunities. It examines case study examples in which preservation has diversified economies and enhanced social cohesion. We argue from a cultural viewpoint, evaluating the economic value of patrimony and how globalisation trends can be used to promote cultural heritage. Observing examples of factors that shaped economic development in some cities, from tourism, infrastructure, transport, health services, entertainment facilities to employment, investments or even innovation. To then reviewing opposing arguments against the digitization of some instruments of heritage. Reaching the final conclusion that affirms the positive economic significance of cultural heritage which has been broadened by technology.